Real‐space analysis of radiation‐induced specific changes with independent component analysis. (22nd February 2018) - Borek, Dominika; Bromberg, Raquel; Hattne, Johan; Otwinowski, Zbyszek
Abstract : The signal representing specific X‐ray radiation‐induced changes in crystals can be separated into distinct and statistically independent components by the independent component analysis method performed in real space. These components can be of native or difference electron density map types and can be interpreted in terms of physical processes and chemical and/or biological reactions. Abstract : A method of analysis is presented that allows for the separation of specific radiation‐induced changes into distinct components in real space. The method relies on independent component analysis (ICA) and can be effectively applied to electron density maps and other types of maps, provided that they can be represented as sets of numbers on a grid. Here, for glucose isomerase crystals, ICA was used in a proof‐of‐concept analysis to separate temperature‐dependent and temperature‐independent components of specific radiation‐induced changes for data sets acquired from multiple crystals across multiple temperatures. ICA identified two components, with the temperature‐independent component being responsible for the majority of specific radiation‐induced changes at temperatures below 130 K. The patterns of specific temperature‐independent radiation‐induced changes suggest a contribution from the tunnelling of electron holes as a possible explanation. In the second case, where a group of 22 data sets was collected on a single thaumatin crystal, ICA was used in another type of analysis to separate specific radiation‐induced effects happening on different exposure‐level scales. Here, ICA identified two components of specific radiation‐induced changes that likely result from radiation‐induced chemical reactions progressing with different rates at different locations in the structure. In addition, ICA unexpectedly identified the radiation‐damage state corresponding to reduced disulfide bridges rather than the zero‐dose extrapolated state as the highest contrast structure. The application of ICA to the analysis of specific radiation‐induced changes in real space and the data pre‐processing for ICA that relies on singular value decomposition, which was used previously in data space to validate a two‐component physical model of X‐ray radiation‐induced changes, are discussed in detail. This work lays a foundation for a better understanding of protein‐specific radiation chemistries and provides a framework for analysing effects of specific radiation damage in crystallographic and cryo‐EM experiments.